Better safe than sorry: The response to a simulated predator and unfamiliar scent by the European hare. (4th March 2020) - Mayer, Martin; Fog Bjerre, Dagmar Hedvig; Sunde, Peter
Abstract: Predator presence can create a "landscape of fear, " which is defined as the spatially explicit distribution of perceived predation risk as seen by prey. Prey species can alter their behavior and space use as a response to increased predation risk, which might be traded off with energetic requirements. Thus, whether or not an anti‐predator behavior is performed might depend on the perceived risk. In this study, we investigated the behavioral and spatial response of the European hare ( Lepus europaeus ) toward the presence of a predator scent, using red fox ( Vulpes vulpes ) scat, an unfamiliar control scent (butyric acid), and a true control (no scent). We collected data on hare activity times and behavior using 50 camera trap locations and spatial data using GPS telemetry (30, 481 GPS positions of 12 hares). Hares showed spatial anti‐predator behaviors within their home range, for example, the local avoidance of areas treated with scent and remaining further from field edges, in response to sympatric predator scent and partly also in response to unfamiliar butyric acid. Conversely, more costly anti‐predator behaviors, that is, increased vigilance at the expense of foraging, were only shown in response to the predator scent. Our results suggest that prey species respond flexibly toward scent cues, utilizing less costly anti‐predator behaviors independent of the perceived threat, whereas costly anti‐predator responses are only used in the presence of "real" threat. Further, our findings emphasize that a combination of camera trap and GPS data can provide detailed information on animal behavior and space use, and caution that interpretation of one data source alone might lead to incomplete conclusions.